2018
DOI: 10.3201/eid2411.162094
|View full text |Cite
|
Sign up to set email alerts
|

Spotted Fever Group Rickettsiae in Inner Mongolia, China, 2015–2016

Abstract: We found Rickettsia raoultii infection in 6/261 brucellosis-negative patients with fever of unknown origin in brucellosis-endemic Inner Mongolia, China. We further identified Hyalomma asiaticum ticks associated with R. raoultii, H. marginatum ticks associated with R. aeschlimannii, and Dermacentor nuttalli ticks associated with both rickettsiae species in the autonomous region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 9 publications
(12 reference statements)
0
17
0
Order By: Relevance
“…A previous study indicated the A. bovis infection of monkeys, suggesting that A. bovis may infect humans [ 46 ]. Rickettsia japonica , which was widely distributed in China (including in Henan [ 40 ], Anhui [ 7 ], Zhejiang [ 47 ], Shandong [ 48 ], and Hubei [ 26 ]) and R. raoultii , which was mainly reported around the border of China (like the Northeastern [ 49 ], Northwestern [ 50 , 51 ], Southwestern [ 52 ], Inner Mongolia [ 53 ], and Central [ 40 ] areas) belonged to the spotted fever group rickettsiae and could cause human fever, vomiting, nausea, maculopapular rash, and occasionally eschars at the site of inoculation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated the A. bovis infection of monkeys, suggesting that A. bovis may infect humans [ 46 ]. Rickettsia japonica , which was widely distributed in China (including in Henan [ 40 ], Anhui [ 7 ], Zhejiang [ 47 ], Shandong [ 48 ], and Hubei [ 26 ]) and R. raoultii , which was mainly reported around the border of China (like the Northeastern [ 49 ], Northwestern [ 50 , 51 ], Southwestern [ 52 ], Inner Mongolia [ 53 ], and Central [ 40 ] areas) belonged to the spotted fever group rickettsiae and could cause human fever, vomiting, nausea, maculopapular rash, and occasionally eschars at the site of inoculation [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, R. raoultii infection cases with increasing numbers have been reported in humans [17][18][19]29]. These rickettsiose patients present not only lethargy, fever, and headache, but also neurological abnormalities [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is parasitic on livestock and can also cause damage to humans [29]. D.nuttalli can carry different pathogens including Babesia, Anaplasma vois, Rickettsia, and Coxellia [30,31,32]. I. persuleatus is the dominant tick species in northeast China.…”
Section: Discussionmentioning
confidence: 99%